Pengaruh terapi musik dalam mengatasi stres siswa pada masa pandemi - Tifaldha Afghedara; Miskanik Miskanik; Fajar Bilqis (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
this study aims to determine the effect of music therapy in dealing with student stress at Malahayati Islamic Vocational School during the pandemic. The research method used in this research is quantitative research with quasi-experimental, and this research model uses nonequivalent control group design. Sampling used purposive sampling technique with a sample size of 60 respondents (30 students in the treatment group and 30 students in the control group). Student stress was measured by giving a questionnaire in the form of a questionnaire about student stress. The data analysis of this research used t-test to determine the difference between the effect of music therapy on the treatment group and the control group on student stress. The results of the t-test analysis shown that there was a significant difference in music therapy between the treatment group and the control group on student stress at Malahayati Islamic Vocational School during the pandemic. This study concluded that music therapy can have an effect on dealing with student stress at the Malahayati Islamic Vocational School during the pandemic.